2015
DOI: 10.1175/jcli-d-14-00746.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Low-Level Atmospheric Moisture Transport Associated with the West African Monsoon

Abstract: The major objective of this study is to re-evaluate the ocean-land transport of moisture for rainfall in West Africa using 1979-2008 NCEP-NCAR reanalysis data. The vertically integrated atmospheric water vapor flux for the surface-850 hPa is calculated to account for total low-level moisture flux contribution to rainfall over West Africa. Analysis of mean monthly total vapor fluxes shows a progressive penetration of the flux into West Africa from the south and west. During spring (April-June), the northward fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 63 publications
13
60
0
1
Order By: Relevance
“…This concords with the penetration of VIMF to the south of the NRB carrying moisture from the Gulf of Guinea (Figure 5b), which is more appreciable in August (Figure 8b). In general the African Sahel is influenced throughout the monsoon period by southerly winds transporting moisture from the Gulf of Guinea [50]. These results are in agreement with similar findings for the NRB by Stohl and James [13].…”
Section: Monthly Budget Of (E -P)i10 Over the Sources And Precipitatisupporting
confidence: 91%
“…This concords with the penetration of VIMF to the south of the NRB carrying moisture from the Gulf of Guinea (Figure 5b), which is more appreciable in August (Figure 8b). In general the African Sahel is influenced throughout the monsoon period by southerly winds transporting moisture from the Gulf of Guinea [50]. These results are in agreement with similar findings for the NRB by Stohl and James [13].…”
Section: Monthly Budget Of (E -P)i10 Over the Sources And Precipitatisupporting
confidence: 91%
“…The observational rainfall dataset used in this study was provided by the national meteorological centers of countries across the region (see Lélé et al 2015). As many as 180 rain gauge-based precipitation observations over WA were used.…”
Section: Datamentioning
confidence: 99%
“…Because the water cycle is an integral part of the global energy cycle, it therefore plays a fundamental role in determining the large-scale circulation and precipitation patterns. In addition, the variability of water availability is one of the most limiting parameters for sustaining life, agriculture, and economic development in the Sub-Saharan WA countries (Lélé et al 2015). Therefore, understanding the WAM climate fluctuations requires an accurate estimation of the hydrological cycle over the region and its linkages to regional-scale features.…”
mentioning
confidence: 99%
“…Along the Gulf of Guinea there is some evidence of a convection belt which The position of the flux reveals that moisture transport over Central Africa is regulated by an enhanced evaporation coming from tropical Atlantic Ocean at the beginning of Kelvin wave's active phase which positively interacts with convection over Atlantic. Previous studies (Lélé et al, 2015) showed that Atlantic Ocean is the mayor source of water vapor and the propagated characteristic is mostly progresses from equator to north and south of the continent and this created a bimodal regime over the continental area. But this cannot explain the fact that propagation characteristics suddenly changed with season, this may be related to the presence of Kelvin waves over the region which influenced propagation of dynamic structures which progressed in opposite direction.…”
Section: Interaction Between Moisture Flux Field Kelvin Waves Eventsmentioning
confidence: 99%
“…They showed that the full column vertically integrated moisture convergence exhibits a bimodal distribution with maximum during the rainy seasons. Lélé et al (2015) evaluated the ocean-land transport of moisture for rainfall in West Africa and showed a pronounced south-west incursion of the flux over West Africa during April-June, while during July-September, the southerly transport weakens, but westerly transport is enhanced. Most studies evaluated the variability of moisture transport and it relationship with precipitation, large-scale or small-scale but the interaction between moisture and equatorials waves like Kelvin waves has not yet been studied and clearly understood in this region.…”
Section: Introductionmentioning
confidence: 99%